The mismeasured price takers: an alternative approach to the Penn World Table measurements of output growth in open economies - Rodriguez Gaudin, J.I. (2023)
The Penn World Table (PWT) builds a measure of welfare that is suitable for com- parisons between countries: real GDP at current PPPs. This measure treats the trade balance component of GDP as a transfer of expenditure between countries. By means of an extension to trade of the two-sector AK model suggested by Rebelo (1991) studied later by Felbermayr and Licandro (2005), we argue that the trade balance of countries re- flects investment from surplus countries to deficit countries, hence, treating it as a transfer of expenditure can be misleading. We show that in the presence of international trade, free capital mobility, specialization, and biased technological progress in favour of capital goods, the PWT growth rate of output provides a biased measure of the growth in welfare. We propose an alternative approach to this welfare measure, to account for capital move- ments between countries. We find that treating trade balance as investment rather than expenditure transferred across countries modify this bias, generating welfare gains and losses between countries. We find that these results are dependant on the share of total traded volume of each country, the country trade balance sign, and the price of invest- ment goods relative to consumption of each country. We find that welfare in developing small open economies with trade balance deficits and high investment prices relative to domestic goods - the price takers - is consistently underestimated in the PWT. Even more, welfare in developed big open economies and higher investment prices relative to domestic goods - the price makers - face almost no corrections between measures of welfare adopted.